Assessing the optimal strategy for dual antiplatelet therapy. (3rd October 2015) - Chang, Lee; Yeh, Robert W
Abstract : Coronary artery disease remains a leading cause of morbidity and mortality worldwide. Each year, millions of patients undergo stent placement to treat coronary artery disease. As stents are prone to thrombosis, which can potentially be devastating, patients are treated with dual antiplatelet therapy with aspirin plus a thienopyridine for at least 6–12 months after stent placement. New evidence suggests that long-term dual antiplatelet therapy beyond 1 year prevents ischemic events but also leads to increased risk of bleeding. To determine the optimal strategy for dual antiplatelet therapy after stent placement, the benefits and risks must be carefully considered and individualized for each patient.